2021
DOI: 10.1021/acsami.1c10842
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Driven Reforming of Lignocellulose into H2 by Intrinsic Monolayer Carbon Nitride

Abstract: The photoreforming of lignocellulose is a novel method to produce clean and sustainable H 2 energy. However, the catalytic systems usually show low activity under ultraviolet light; thus, this reaction is very limited at present. Visible light-responsive metal-free two-dimensional graphite-phased carbon nitride (g-C 3 N 4 ) is a good candidate for photocatalytic hydrogen production, but its activity is hindered by a bulky architecture. Although reported layered g-C 3 N 4 modified with active functional groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…16,17 However, up to now, only a few studies of g-C 3 N 4based PR of cellulose into H 2 have been reported. [18][19][20] These works also achieved their PR reactions by dissolving cellulose using strong alkaline conditions, confirming that achieving PR of cellulose under neutral conditions using g-C 3 N 4 as photocatalyst is desirable but challenging. It is documented that bulk g-C 3 N 4 (BCN) can be fabricated directly by thermal polymerization of various inexpensive precursors, but it has a relatively small surface area and low charge separation efficiency, thereby significantly limiting its photoreactivity.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…16,17 However, up to now, only a few studies of g-C 3 N 4based PR of cellulose into H 2 have been reported. [18][19][20] These works also achieved their PR reactions by dissolving cellulose using strong alkaline conditions, confirming that achieving PR of cellulose under neutral conditions using g-C 3 N 4 as photocatalyst is desirable but challenging. It is documented that bulk g-C 3 N 4 (BCN) can be fabricated directly by thermal polymerization of various inexpensive precursors, but it has a relatively small surface area and low charge separation efficiency, thereby significantly limiting its photoreactivity.…”
Section: Introductionmentioning
confidence: 69%
“…Graphitic‐like carbon nitride (g‐C 3 N 4 ), a typical metal‐free semiconductor that originally emerged for photocatalytic H 2 production from water in 2009, 15 has been considered as a desirable candidate for PR because of its visible‐light response, nontoxicity, excellent stability and tunable optical features 16,17 . However, up to now, only a few studies of g‐C 3 N 4 ‐based PR of cellulose into H 2 have been reported 18‐20 . These works also achieved their PR reactions by dissolving cellulose using strong alkaline conditions, confirming that achieving PR of cellulose under neutral conditions using g‐C 3 N 4 as photocatalyst is desirable but challenging.…”
Section: Introductionmentioning
confidence: 99%
“…NCN CN x Lignin Simulator –/100 25 1.6 0.16/4.3 M, KPi 40.8 [ 52 ] Pt-. NCN CN x Lignin Simulator –/100 25 1.6 0.16/10 M, KOH 14.5 [ 52 ] Pt/g-C 3 N 4 Lignin Xe 300/100 5 5 5/pH = 10 20.75 [ 53 ] NiS/CdS Lignin Xe 300/ 25 1 0.1/lactic acid 147.6 44.9/–λ ≥ 400 nm [ 51 ] Pt/TiO 2 Poplar wood Xe 300/– 0.4 4 26 [ 47 ] Pt/TiO 2 Pinewood Simulator –/200 160 30.0 …”
Section: Current State Of the Researchmentioning
confidence: 99%
“…Visible light-responsive photocatalysts such as sulfides ( E bg = ⁓2.4 eV CdS [ 38 , 50 , 51 ]) and carbon nanomaterials ( E bg = ⁓2.7 eV for graphitic carbon nitride [ 52 , 53 ]) have also been developed for H 2 generation from photo-reforming of lignocellulosic substrates. 1D CdS nanowires (NWs) were prepared and loaded with NiS 2 by a two-step hydrothermal method.…”
Section: Current State Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation